2021
DOI: 10.1002/adfm.202101036
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yield and Low‐Cost Solar Water Purification via Hydrogel‐Based Membrane Distillation

Abstract: As an eco‐friendly means, solar water purification has attracted substantial research interest regarding material design, system engineering, and energy management. However, the low water yield and relatively high cost essentially restrict its practical potential. Here, a hydrogel‐based ultrathin membrane (HUM) is developed to synergistically coordinate facilitated vapor transfer and environmental energy harvesting for solar‐driven membrane distillation. The evaporation front is directly exposed to an airflow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 50 publications
0
79
0
1
Order By: Relevance
“…It is reported that the carbon black can be treated by a concentrated HNO3 solution to improve its hydrophilicity and the dispersibility in water. 96 Considering the simple processing method and low cost of HNO3, the carbon black can be arguably considered a low-cost material. Combing with a reasonable light path and design, the evaporation rate of these materials can reach 3.86 kg m -2 h -1 , and the energy conversion efficiency is as high as 92%.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the carbon black can be treated by a concentrated HNO3 solution to improve its hydrophilicity and the dispersibility in water. 96 Considering the simple processing method and low cost of HNO3, the carbon black can be arguably considered a low-cost material. Combing with a reasonable light path and design, the evaporation rate of these materials can reach 3.86 kg m -2 h -1 , and the energy conversion efficiency is as high as 92%.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…Carbon-based materials have been used as solar absorbers in various studies in recent years, owing to their excellent light absorption over a broad spectrum, ease of preparation, abundance and low cost. Carbon-based materials include activated carbon, 83–86 polymer 76,87–90 or biomass 82,91–95 derived carbide, carbon black 96–101 and various amorphous carbon materials and highly graphitized carbon materials, such as graphene, 56,59,63,74,77,102–122 carbon nanotubes (CNTs) 27,123–130 and their derivatives.…”
Section: Solar–thermal Conversion Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Consiste en pasar una corriente salina caliente y una corriente de agua fría desalinizada separadas por una membrana porosa y aprovechar la diferencia en las presiones de vapor para lograr que las moléculas de vapor de agua pasen de la corriente de agua salada hacia el lado del agua pura [51,52,53,54,55,56]. La membrana es de naturaleza hidrofóbica y debido al tamaño de los poros, ni el agua líquida ni las sales pueden atravesarla.…”
Section: Electrodiálisis (Ed)unclassified
“…[ 8 ] Although the collection installations much larger than the evaporation area and with auxiliary facilities (e.g., airflow assistances, extra condensers) are able to reduce local humidity for a closed system, high capital, and operating costs will be involved, restricting their industrial applications considerably. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%